Cedar seedlings dependency and responsiveness to arbuscular mycorrhizal fungi - Rocha, Fabiano Souza; Júnior, Orivaldo José Saggin; Silva, Eliane Maria Ribeiro da; Lima, Wallace Luís de (Pesquisa Agropecuaria Brasileira, 2006)
The objectives of this work were to evaluate cedar (Cedrela fissilis Vell.) seedlings responsiveness to arbuscular mycorrhizal fungi (AMF) species and to determine mycorrhizal dependency degree of this seedling. The experiment was carried out at greenhouse, in a complete randomized block design as a factorial set 5 (P doses) x 5 (4 AMF species + noninoculated treatment) with six replications. Glomus clarum was the most efficient AMF species in promoting the growth and P nutrition of cedar seedlings, especially when the inoculation was done in substratum containing P available levels close to 12 mg dm-3. The saving of applied P was approximately 63%, regarding noninoculated treatment when 80% of the maximum growth was estimated. The elevated degree of mycorrhizal dependency of cedar seedlings was verified, so AMF inoculation is a procedure that should be considered in nursery stage, in order to guarantee cedar seedlings successful establishment and growth on field conditions.